Profil Daya Tahan Jantung Paru Anggota Club Hapkido Esa Keter Martialart Academy Minahasa Tahun 2024 - Polii G; Berhimpong M; Pangemana M (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Evaluation of the cardiorespiratory endurance condition of Hapkido athletes at Dojang Esa Ter Martial Arts Academy by using the bleep test (multi-stage fitness test). According to science for sport, the multi-stage fitness test is a test to measure cardiopulmonary endurance to determine an athlete's maximum oxygen intake. Apart from that, the coach also evaluates the condition of the athletes' cardiorespiratory endurance through sparring sessions by paying attention to performance and duration during sparring sessions. The aim of the research was to determine the lung endurance profile of athletes in the Hapkido martial arts sport at Dojang Esa Ter Martial Arts Academy. The type of research that the researcher used was descriptive research. This was intended to describe the cardiopulmonary endurance profile of members of the Hapkido Esa Ter Martial Arts Academy martial arts club with a sample size of 30 respondents. Based on the research results, it was found that 3 athletes or (10%) of them had very poor heart endurance, then 3 athletes or (10%) of them had very poor cardiopulmonary endurance, then 11 athletes or (36.7% ) of them have sufficient cardiopulmonary endurance, then 2 athletes or (6.7%) of them have good cardiopulmonary endurance, and the remaining 11 athletes or (36.7%) of them have very good cardiopulmonary endurance. Good.